Relationship between duration of treatment and urine protein in pulmonary tuberculosis patients - Sadid, Randy; Salim, Maulidiyah; Nuswantoro, Ari; Yunus, Mohd (Borneo Scientific Publishing, 2025)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. TB treatment is an efficient way to prevent the spread of the bacteria. The goals of TB treatment include curing, maintaining the patient's quality of life and productivity, preventing death from active TB or its sequelae, preventing relapse, reducing transmission to others, and preventing drug resistance. Most TB patients complete treatment without significant side effects, but a minority experience significant side effects. The duration of drug consumption can affect other organs such as the kidneys. Proteinuria is a condition in which there is protein in the urine beyond normal limits. The purpose of this study was to determine the relationship of length of treatment to urine protein in TB patients in Meliau District. This research method is analytical observational with a cross-sectional approach and consecutive sampling technique, with a total sample of 47 respondents. The results showed 10 respondents (21.27%) experienced proteinuria, while 37 respondents (78.73%) did not. Chi-Square analysis showed a relationship between length of treatment and urine protein in TB patients in Meliau District, as evidenced by a p-value of 0.015 (<0.05). In conclusion, there is a relationship between length of treatment and urine protein in TB patients in Meliau District.